2017
DOI: 10.1002/mus.25408
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical aspects of immigrants with myasthenia gravis in northern Europe

Abstract: Our findings indicate that Asian immigrant MG patients carry genetic factors or environmental/lifestyle factors which contribute to their specific phenotype, even after migration. Muscle Nerve 55: 819-827, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(34 reference statements)
2
5
0
1
Order By: Relevance
“…In agreement with previous findings, 13 we also observed a sex-related bias in our study, in that female patients outnumbered male patients. A majority of patients from both sexes had an EOMG; in the LOMG group, male patients outnumbered female patients, which is in line with the report by Al-Moallem et al 5 However, contrary to previous studies from the United States, Europe, and South Africa, and studies performed on Dutch and Norwegian patients that have consistently shown a bimodal peak of onset for females and a late single peak for males, 14 we did not observe a second peak of MG onset after 50 years of age in males or females in our cohort. This may be attributed either to environmental factors or to differences in ethnicity and racial composition.…”
Section: Resultssupporting
confidence: 88%
“…In agreement with previous findings, 13 we also observed a sex-related bias in our study, in that female patients outnumbered male patients. A majority of patients from both sexes had an EOMG; in the LOMG group, male patients outnumbered female patients, which is in line with the report by Al-Moallem et al 5 However, contrary to previous studies from the United States, Europe, and South Africa, and studies performed on Dutch and Norwegian patients that have consistently shown a bimodal peak of onset for females and a late single peak for males, 14 we did not observe a second peak of MG onset after 50 years of age in males or females in our cohort. This may be attributed either to environmental factors or to differences in ethnicity and racial composition.…”
Section: Resultssupporting
confidence: 88%
“…These data may further support the observation of a general increase in the incidence of autoimmune diseases in general and the high rate of autoimmune diseases in Israel in particular. As the pathogenesis of MG is thought to be influenced by a combination of genetic and environmental factors, 43‐45 one may speculate that our findings, also observed in other studies, 16‐18,22‐23,32‐36,38,46‐50 can be attributed to changes in environmental factors such as exposure to infective pathogens, diet, and contact with ecological compounds.…”
Section: Discussionsupporting
confidence: 86%
“…If confirmed, a younger manifestation age may hint to an increased risk for thymoma and thymoma-associated MG development in Indians. In fact, the proportion of thymoma patients among MG patients was found to be higher in some Asian countries compared to Northern European countries ( 18 - 20 ).…”
Section: Discussionmentioning
confidence: 94%